Symphony gives memorable performance - Donati, Marilyn (Raton, NM Raton Range, 1993)
Article is a review of the New Mexico Symphony Orchestra held at the Shuler Theater on February 23, 1993.
Newspaper article
Master list item #: 22
File location is in the Raton file Cabinet
Keywords: Melone, Roger -- Conductor; Connolly, Kevin -- Violin Virtuoso; New Mexico Symphony Orchestra; Music Performances; Arts and Humanities Council; Symphonies; Shuler Theater; Raton, New Mexico